Growth response of sprouted rubber seeds to pre-plant application of diuron - Lakshmanan R; Punnose K I (Indian Journal of Natural Rubber Research, 1998)
Pot culture and field experiments were carried out to study the tolerance of sprouted seeds of Hevea brasiliensis to preplant application of diuron at the rate of 2.5kg/ha. Results of the pot culture study, where planting was carried out the same day and 1, 3, 5 or 7 days after spraying indicated no toxic effect on seedling growth. On the contrary, a slight stimulatory effect on diuron on seedling, growth was noticed. Field experiments revealed that growth of rubber was not adversely affected when planted at different intervals( same day, 1, 2, 3, 4, 5, 7 or 10 days) after spraying diuron.
Keywords: Diuron; Diuron; Herbicide; Herbicide; Hevea; Hevea; Seedling growth; Seedling growth; Sprouted seed; Sprouted seed; Weed control; Weed control